Robust finite-time connectivity preserving coordination of second-order multi-agent systems - Sun, Chao (2020)
In this paper, we consider robust finite-time connectivity preserving coordination problems for second-order multi-agent systems with limited sensing range. Based on integral sliding mode control and artificial potential field, a distributed controller is developed to achieve robust finite-time consensus and meanwhile maintain the connectivity of the communication network. The method is further extended to address a finite-time formation tracking control problem. Numerical examples are given to show the effectiveness of the proposed methods.